AB1239 THE EFFECT OF INFLUENZA VACCINATION ON THE MULTI-BIOMARKER DISEASE ACTIVITY SCORE AND ITS COMPONENT BIOMARKERS IN HEALTHY SUBJECTS. (2nd June 2020) - Furst, D.; Lenz, L.; Horton, M.; Flake, D.; Sasso, E.; Weinblatt, M. E.
Abstract : Background: The multi-biomarker disease activity (MBDA) blood test measures 12 protein biomarkers (IL-6, CRP, SAA, EGF, VEGF, VCAM, MMP-1, MMP-3, leptin, resistin, TNF-RI and YKL40). It uses a validated algorithm to provide a score on a scale of 1-100 for assessing disease activity in patients with rheumatoid arthritis (RA). The MBDA score reflects several molecular aspects of inflammation, including cytokines, acute phase reactants, growth factors, molecular adhesion, metalloproteinases and hormones. Insights gained by understanding how vaccination affects these biomarkers in healthy subjects - in whom the level of inflammation prior to vaccination should be low and stable - may aid the understanding of how vaccination affects patients with RA. Objectives: The goal of this study was to understand how immunization of healthy subjects with the influenza vaccine affects the assessment of inflammation with the MBDA score and its 12 biomarkers. Methods: A 4-strain influenza virus vaccine (Fluarix Quadrivalent, GlaxoSmithKline) was administered intramuscularly to 22 healthy volunteer subjects on October 24, 2018. Serum samples were obtained immediately prior to vaccination (baseline) and 1, 2 and 3 weeks after vaccination. No restrictions were placed on subject activity. Samples were stored at -80 o C until measurement of the 12 MBDA biomarkers for determination of the adjusted MBDA score, hereafter called the MBDA score. (Adjustment accounts for the effects of age, sex and adiposity 1 ). MBDA scores (natural scale) and biomarker concentrations (log scale) were modeled using generalized estimating equations (GEE) that account for correlations between measurements from the same subject at multiple timepoints. Significance of MBDA score change or biomarker concentration change over time was determined by a likelihood ratio test of timepoints. Results: Of the 22 healthy subjects receiving the influenza virus vaccine, 14 (63.6%) were female, with mean (SD) age of 40.0 years (8.9). MBDA scores were low (<30), moderate (30-44) or high (>44) for 15 (68%), 6 (27%) and 1 (5%) subjects at baseline, and this distribution was stable over time (Figure 1 ). Overall, MBDA scores did not change significantly over time (p=0.48, Figure 2 ). Mean changes in MBDA score (95% CI) from baseline to weeks 1, 2 and 3 were 0.32 (-3.07, 3.71), 0.82 (-3.03, 4.67) and 2.86 (-1.10, 6.82), respectively (Figure 2 ); the week 3 value becomes 0.95 (-1.78, 3.68) if the week 3 outlier is removed. Among the 66 post-baseline measurements of change in MBDA score (Figure 2 ), 3 (5%) exceeded the 95% CI for change in MBDA score in this study (i.e., 14). When assessing the entire cohort across all timepoints, EGF was the only biomarker that demonstrated statistically significant change over time (p=5.6 x 10 -7 ). At weeks 1, 2 and 3, the mean relative concentrations of EGF, compared with baseline, were 0.62 (0.52, 0.74), 0.86 (0.70, 1.06) and 0.62 (0.50, 0.76), respectively. Conclusion: Immunization of 22 healthy subjects with a quadrivalent influenza vaccine did not have a statistically significant effect on MBDA scores during a 3-week observation, and it had minimal effect on the component biomarkers. References: [1]Curtis et al. Rheumatology [Oxford] 2018;58:874 Disclosure of Interests: Daniel Furst Grant/research support from: AbbVie, Actelion, Amgen, BMS, Corbus Pharmaceuticals, the National Institutes of Health, Novartis, Pfizer, and Roche/Genentech, Consultant of: AbbVie, Actelion, Amgen, BMS, Cytori Therapeutics, Corbus Pharmaceuticals, the National Institutes of Health, Novartis, Pfizer, and Roche/Genentech, Speakers bureau: CMC Connect (McCann Health Company), Lauren Lenz Shareholder of: Myriad Genetics, Inc., Employee of: Myriad Genetics, Inc., Megan Horton Shareholder of: Myriad Genetics, Inc., Employee of: Myriad Genetics, Inc., Darl Flake Shareholder of: Myriad Genetics, Inc., Employee of: Myriad Genetics, Inc., Eric Sasso Shareholder of: Myriad Genetics, Inc., Employee of: Myriad Genetics, Inc., Michael E. Weinblatt Grant/research support from: BMS, Amgen, Lilly, Crescendo and Sonofi-Regeneron, Consultant of: Horizon Therapeutics, Bristol-Myers Squibb, Amgen, Abbvie, Crescendo, Lilly, Pfizer, Roche, Gilead